Điểu khiển thích nghi các hê thống phi tuyến cấu trúc thay đổi sử dụng hệ thống mờ nơ ron. - Hỷ, Chu Văn (Journal of Computer Science and Cybernetics, 2016)
In this paper, we present a method of nonlinear variable structure system control using neural fuzzy systems. All inverse model adaptive control scheme IS chosen. A neural fuzzy system with 011-line supervised structure and parameter learning (adapted from C.T. Lin. C.S.G. Lee) is analysed.